A novel stormwater management system for urban roads in China based on local conditions. (May 2018) - Cheng, Yuning; Wang, Ruijun
Highlights: We introduce a newly structured SWM system for urban roads. The special collecting method can effectively separate litter and debris. The storage facility has an extra function of irrigating without power input. Data analysis indicates that the designed system performed well in retaining rainwater on site. A comparative analysis proves that the irrigation method generally achieved its expected effect. Abstract: This study introduces a novel design for stormwater management (SWM) for urban roads in China on basis of issues that have emerged in recent years. The designed system allows for the management of rainwater, from collection to reuse, in a way that is highly cost-effective and sustainable. Supported by the local government, a 600-m road section implementing the design was built and operated in Nanjing, China, in 2015. Data analysis supported the good evaluation of the current system performance, which was basically as expected. Specifically, about one-third to one-half of rainfall was captured during the rainy season. The system structure presented a continuous stability, even in rare heavy rain events. The irrigation function was realized using a slow-release method without any power input. The proposed design offered practical uses during rainless periods, thus had an ability to generally substitute for the conventional irrigation.